Inflation Targeting and Economic Performance: Application of the New Keynesian Small Open Economy DSGE - Habiby, salwa (Advances in Social Sciences Research Journal, 2022)
Bank Al-Maghrib aim to adopt the inflation targeting regime to keep pace with changes in the monetary policy environment. The challenge for the central bank is to meet the prerequisites of inflation targeting to ensure the anchoring of expectations, and thus achieve the inflation target and real stability. The objective of this paper is to propose an optimal model for Morocco’s successful transition to inflation targeting. To do so, we build a New Keynesian Small Open Economy DSGE model, characterized by financial frictions, imperfect exchange rate pass-through, unemployment, fiscal rule and new shocks. The results of our simulations lead us to assert that it would be wise to choose the most complete model, since it provides credibility, stability and growth. Keywords: anchoring expectations, inflation targeting, economic growth, DSGE, financial frictions.